1987
DOI: 10.1099/00221287-133-7-1783
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Elastolytic Protease of Vibrio vulnificus

Abstract: Large amounts of a highly purified, extracellular elastolytic protease of Vibrio vulnificus were obtained by sequential ammonium sulphate precipitation and hydrophobic interaction chromatography with phenyl-Sepharose CL-4B. The protease had an Mr of about 50,500 (estimated by SDS-PAGE), a pI of 5.7, and a temperature optimum range of 55 to 60 degrees C. The pH optimum and the results of inactivation studies suggested that the enzyme was a neutral metalloprotease. The protease had about 429 amino acid residues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
1
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 12 publications
5
139
1
1
Order By: Relevance
“…These results suggested that the V. vulnificus protease was a metalloprotease and Zn2+ and/or Fe2+ were essential for its enzyme activity. The existence of caseinolytic, collagenolytic and elastolytic protease (s) produced by V. vulnificus has been reported (11,13,25). Kothary and Kreger (11) partially purified the elastolytic protease and reported that the elastolytic and caseinolytic activities were inseparable in their fractionation.…”
Section: Amino Acid Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that the V. vulnificus protease was a metalloprotease and Zn2+ and/or Fe2+ were essential for its enzyme activity. The existence of caseinolytic, collagenolytic and elastolytic protease (s) produced by V. vulnificus has been reported (11,13,25). Kothary and Kreger (11) partially purified the elastolytic protease and reported that the elastolytic and caseinolytic activities were inseparable in their fractionation.…”
Section: Amino Acid Analysismentioning
confidence: 99%
“…vulnificus is known to produce many toxic or pathogenic factors, such as cytolysin (8,13,23), protease (11,13,25), phospholipase A2 (27), and siderophores (24). However, in the pathogenesis of V. vulnificus infection, the actual role of any product has not been clarified yet.…”
mentioning
confidence: 99%
“…have been studied in detail. Vibrio vulnificus, which causes wound infections and septicaemia in humans, produces a neutral metalloprotease with elastolytic activity (Kothary & Kreger, 1987) that has elicited dermonecrosis (Smith & Merkel, 1982). Vibrio cholerae haemagglutinin/protease nicks and activates the A subunit of the cholera enterotoxin (Booth et al, 1984), and shows…”
Section: Introductionmentioning
confidence: 99%
“…An aphA homolog was identified in V. vulnificus (56), and although expression of this gene was not directly affected by Qrrs, it was repressed by SmcR. 3 We speculate that there are other as yet unidentified regulatory proteins that are activated at low cell density in V. vulnificus. Qrrs are expressed at low cell densities and derepressed under iron-limiting conditions, suggesting that they may play a role in the regulation of genes required under these conditions.…”
Section: Discussionmentioning
confidence: 99%